Transdermal Delivery of Adipocyte Phospholipase A2 siRNA using Microneedles to Treat Thyroid Associated Ophthalmopathy-Related Proptosis. (19th April 2021) - Liu, Guiqin; Deng, Yan; Song, Yi; Sui, Yi; Cen, Juan; Shao, Ziyu; Li, Hu; Tang, Tao
Thyroid associated ophthalmopathy (TAO) is an organ-specific autoimmune disease occurring in patients with thyroid disease. Patients with TAO-related proptosis is largely due to excessive orbital adipose tissue Adipocyte phospholipase A2 (AdPLA) is one of the most important regulatory factors in adipocyte lipolysis, which may be associated with TAO-related proptosis. Thus, silencing AdPLA by RNA interference may be beneficial for the treatment of TAO. In this study, we sought to evaluate the efficiency of two types of microneedles to deliver siRNAs for silencing AdPLA. Our results showed that AdPLA mRNA was up-regulated in the orbit adipose tissues from TAO patients. Silence of AdPLA by siRNA can reduce lipid accumulation in both human and mouse adipocyte cell lines. Moreover, silence effects of silicon microneedle array patch-based and injectable microneedle device-based siRNA administration were examined at the belly site of the mice, and injectable microneedle device showed higher knockdown efficiency than silicon microneedle array patch. This study sets the stage not only for future treatment of TAO-related proptosis using AdPLA siRNA, but also provides the foundation for targeted siRNA delivery by using microneedles.